Star Trek : discovery -- adventures in the 32nd century - Johnson, Mike (Comic book author) (IDW Publishing, 2022)
"Uncover new stories of four fan-favorite characters! First up, Grudge - who is very much a queen and NOT a cat - works tirelessly to keep her interplanetary courier/working human, Cleveland Booker, safe. Next, witness the heart-wrenching history that brought Adira Tal to Discovery and how they were paired with one of the last remaining Trill symbionts. Then, while on a mysterious mission to a frozen world, Lieutenant Commander Detmer encounters the last person she expects to find: herself! And, in the finale, Saurian Lieutenant Linus has never truly fit in with his Starfleet colleagues, but an encounter with an undiscovered species will put all their fates, and the ship's, in his hands! "--Page 4 of cover.